الدعوة إلى الآداب الإجتماعية والخلقية في ضوء الأمثال القرآنية: The Call to Social Etiquette and Morality in the Light of Quranic Proverbs (Al-Qamar, 2021)
The research discussion the social etiquette and morality in the light of Quranice Example, It is Includes the introduction to the concept of proverbs in literal and terminologically, as the research discusses the benefits of proverbs, and describes the types in brief. And as it also involves the call to social etiquette and morality in the light of the Quranic Example as these proverbs can be used as a source of propagating the da'wah to build the Islamic community.
Keywords: Building; Islamic Society; morality; social etiquette; Quranic Example